INITIAL ANALYSIS OF STUDENTS' SCIENTIFIC LITERACY ON DYNAMICS OF PARTICLE MOTION - Putri, Mayang Wahyuni (Department of Physics Universitas Negeri Padang, 2024)
One of the most important abilities in the 21st century is scientific literacy. This research is to analyze students' initial physics science literacy abilities in the dynamics of particle motion. The research method used was descriptive quantitative with a sample of 30 students of class XI phase F.7 at SMAN 2 Solok. Data processing is obtained from two categories, namely student tests and teacher questionnaires. From the results of the student test analysis, the indicator for explaining phenomena scientifically is 61% in the